Description of three new species of Psilotreta (Trichoptera: Odontoceridae) from Japan - Kawase, Naoki (Zootaxa, 2021)
Three new species of the caddisfly genus Psilotreta (Trichoptera: Odontoceridae) from Japan are described: P. voluta sp. nov., P. moritai sp. nov., and P. flavida sp. nov. These three species are easily distinguishable by the male genitalia from previously known Japanese species, P. japonica (Banks 1906) and P. kisoensis Iwata 1928. The three new species are similar to P. vertebrata Yuan et al. 2008, P. cuboides Yuan et al. 2008, and P. excavata Yuan et al. 2008 from the Chinese mainland, and P. clyssan Malicky 2014 from Taiwan, in the shapes of the lateral processes and intermediate appendages of segment X of the male genitalia, but can be distinguished from these species and each other. All Japanese species of Psilotreta listed above belong to the P. chinensis Species Group.